Reconsidering Sites and Services : A Global Review - World Bank (Washington, DC, 2022)
With African cities urbanizing rapidly, there is a growing appreciation that it is time to take a fresh look at the potential for the sites and services approach to meet urban development and housing needs in these rapidly growing urban areas. The report presents guiding principles on designing sites and services projects for Task Team Leaders (TTLs) and operations teams that emerge from a study conducted by the Urban Poverty, Inclusive Cities and Housing Global Solutions Group (GSG). The report provides a clear understanding of the large scale 1st generation sites and services by assessing their design and implementation, establishing their effectiveness in meeting the set objectives, examining reasons most governments and donors abandoned the intervention, identifying factors that contributed to their success or failure in countries where they were adopted, and identifying how building technologies, land and housing markets have changed over time in support of or against sites and services. The report also presents low-carbon alternatives that can be applicable in this approach, before concluding with lessons and potential guiding principles for possible future projects.